2019
DOI: 10.3168/jds.2018-15398
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield loss in response to feed restriction is associated with mammary epithelial cell exfoliation in dairy cows

Abstract: In dairy cows, feed restriction is known to decrease milk yield by reducing the number of mammary epithelial cells (MEC) in the udder through a shift in the MEC proliferation-apoptosis balance, by reducing the metabolic activity of MEC, or both. The exfoliation of MEC from the mammary epithelium into milk is another process that may participate in regulating the number of MEC during feed restriction. The aim of the present study was to clarify the mechanisms that underlie the milk yield loss induced by feed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…As in bovines [19,36], LC showed a gradual drop across parities but curves shapes of different parities were similar (Figure 2). In fact, again, older (multiparous) buffaloes are usually characterized by aged tissues, impaired udder epithelial integrity, greater milk SCS, lower milk LC, and poorer udder health compared to primiparous [18,[36][37][38].…”
Section: Analysis Of Variancementioning
confidence: 99%
“…As in bovines [19,36], LC showed a gradual drop across parities but curves shapes of different parities were similar (Figure 2). In fact, again, older (multiparous) buffaloes are usually characterized by aged tissues, impaired udder epithelial integrity, greater milk SCS, lower milk LC, and poorer udder health compared to primiparous [18,[36][37][38].…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Accordingly, a recent study showed no carryover effect of a 20% feed restriction of 4 weeks (Herve et al, 2018). This lack of persistent effect on milk yield was observed despite the negative effect of feed restriction on the number of MEC in the mammary tissue (as indicated by a higher rate of MEC exfoliation into milk; Herve et al, 2018). It is noteworthy that this was accompanied by an increase in the release of prolactin into blood at milking when cows were switched back to an ad libitum diet.…”
Section: S59mentioning
confidence: 97%
“…No carryover effect on milk yield has been observed regardless of the duration of the dietary challenge (from 4 days to 4 weeks; Friggens et al, 1998;Bjerre-Harpøth et al, 2012) and the stage of lactation (early, mid-or late lactation; Bjerre-Harpøth et al, 2012). Accordingly, a recent study showed no carryover effect of a 20% feed restriction of 4 weeks (Herve et al, 2018). This lack of persistent effect on milk yield was observed despite the negative effect of feed restriction on the number of MEC in the mammary tissue (as indicated by a higher rate of MEC exfoliation into milk; Herve et al, 2018).…”
Section: S59mentioning
confidence: 98%
See 2 more Smart Citations